Wali Nikah Anak Perempuan Tanpa Ayah: (Analisis Pendekatan Teori Double Movement) - Nadziroh, Umi; Isnaeni, Ahmad; Hendro, Beko (AT-TAISIR: Journal of Indonesian Tafsir Studies, 2024)
This article discusses the problem of marriage in Indonesia, especially regarding the role of parents of adopted children as marriage guardians, which is still an issue among the community. This study aims to answer two main questions, How are the interpretations of Qur'anic verses according to tafsir scholars about marriage guardians, and who has the right to be a marriage guardian for adopted children in the present context? To answer these questions, the researcher uses Fazlur Rahman's double movement theory as a conceptual framework to understand the historical context of related verses, such as those found in surah Al-Baqarah: 231, 232, and surah An-Nur: 3. The method used is qualitative with a library research approach and descriptive analysis technique. Researchers used al-Farmawi's thematic interpretation approach to collect relevant verses, as well as the content analysis method to analyze existing texts. This research also contextualizes the understanding into the current social situation of society. The results show that in the current context, the role of guardians in marriage remains relevant as a form of protection and preservation of women's honor, as has been confirmed by the scholars of tafsir. In addition, when the nasab guardian (legally entitled guardian) cannot be present or is obstructed, then the right of guardianship passes to the judge's guardian, including in the case of adopted children's marriage. This research makes an important contribution to the discourse on Islamic marriage law by emphasizing that the principle of guardianship is an essential part of protecting women's rights in marriage, both in the context of the past and the present.